2003
DOI: 10.1007/bf02704317
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic behaviour of semiconducting tin monosulphoselenide single crystals

Abstract: Single crystals of ternary mixed compounds of group IV-VI in the form of a series, SnS x Se 1-x (where x = 0, 0⋅ ⋅25, 0⋅ ⋅50, 0⋅ ⋅75 and 1), have been grown using direct vapour transport technique. The grown crystals were characterized by the X-ray diffraction analysis for their structural parameter determination. All the grown crystals were found to be orthorhombic. The microstructure analysis of the grown crystals reveals their layered type growth mechanism. From the Hall effect measurements Hall mobility, H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Second, unlike the isotropic Pb-chalcogenides, the modeling of transport properties on polycrystalline SnSe in this study is subject to the degree of texturing: theoretically maximum zT can be only achieved when single crystal SnSe is grown and measured along the preferred direction. We notice that independent studies [36][37][38] have reported for single crystal SnSe a Hall mobility of $120 cm 2 V À1 s À1 perpendicular to the c-axis (denoted a-axis in ref. 15), a three-fold difference compared with the highest mobility found in this study, while only a quarter 36 to a half 38 of this along the c-axis.…”
Section: à3mentioning
confidence: 77%
“…Second, unlike the isotropic Pb-chalcogenides, the modeling of transport properties on polycrystalline SnSe in this study is subject to the degree of texturing: theoretically maximum zT can be only achieved when single crystal SnSe is grown and measured along the preferred direction. We notice that independent studies [36][37][38] have reported for single crystal SnSe a Hall mobility of $120 cm 2 V À1 s À1 perpendicular to the c-axis (denoted a-axis in ref. 15), a three-fold difference compared with the highest mobility found in this study, while only a quarter 36 to a half 38 of this along the c-axis.…”
Section: à3mentioning
confidence: 77%
“…Both SnS and SnSe have the Pmcn crystal structure with an orthorhombic unit cell comprising of puckered layers [22], and the lattice parameters of SnSxSe1-x has been experimentally shown to vary gradually across the alloy compositions [23]. The 2x2 supercells of SnS, SnSe, and a representative SnS0.5Se0.5 alloy are presented in Fig.…”
mentioning
confidence: 99%
“…1a. Using the fitted lattice parameters from [23] and adopting the simplest case of homogeneous alloying [16], our density functional theory (DFT) calculations yield band structures with two local band gaps along the ΓY and ΓX axes, denoted by Eg,ΓY and Eg,ΓX respectively, across the whole compositional range ( Fig. 2 and Fig.…”
mentioning
confidence: 99%
“…SnS x Se (y−x) compounds have caught the attention of researchers because of the possibility to tailor the bandgap energy, from 0.9 eV to 2.02 [8][9][10], which makes them adequate for applications where either high optical absorbance or high optical transmittance is needed. Also, n-type and p-type conductivities have been obtained for these materials [11,12]. These two results make these ternary compounds suitable for its use as part of solar cells and photoelectrochemical solar cells [13], phototransistors [14], high-performance thermoelectric material [15], ultrafast laser [16], a high capacity anode for batteries [17], etc.…”
Section: Introductionmentioning
confidence: 80%
“…These two results make these ternary compounds suitable for its use as part of solar cells and photoelectrochemical solar cells [13], phototransistors [14], high-performance thermoelectric material [15], ultrafast laser [16], a high capacity anode for batteries [17], etc. This set of compounds has been deposited by different techniques, some of them to obtain single crystals, thin films and 2D materials like direct vapor transport technique [12], solid synthesis [18], iodine vapor transport [19,20], transport reaction [21], thermal treatment [22] and electrodeposition [13,23]. SnS x Se (2-x) compounds are a family of semiconductors with a hexagonal crystal structure, directly related to the binary compounds SnSe 2 and SnS 2 which has a CdI 2 -type structure with space group P-3m1 and it is well known because of its particular structure, which is composed of atomic layers bonded one to another through Van der Waals interactions that promote the formation of flakes.…”
Section: Introductionmentioning
confidence: 99%